Timing of Heparin and Thrombus Formation in Donor Lungs after Cardiac Death - Keshava, Hari B.; Farver, Carol F.; Brown, Chase R.; Shafii, Alexis E.; Murthy, Sudish C.; Yun, James J.; Vakil, Nakul; Pettersson, Gosta B.; Mason, David Park (The Thoracic and Cardiovascular Surgeon, 2013)
Background Heparin is routinely administered to brain-dead donors before cardiac arrest, although it is not universally allowed for donation after cardiac death (DCD) donors due to concerns that death may be hastened. The lack of heparin may lead to thrombosis and compromised graft function. We evaluated the impact of timing of heparin administration and thrombi formation in a DCD pig model.Methods Eight domestic adult pigs were administered systemic heparin (30,000 IU): four prior to cardiac arrest through intravenous injection (prearrest heparin) and four after cardiac arrest via injection into the right atrium followed by open cardiac massage (postarrest heparin). Pigs were euthanized with potassium chloride and a minimum of 5 minutes of cardiac silence allowed before organ procurement. Lungs were flushed with antegrade and retrograde Perfadex, and pulmonary preservation solution effluent was evaluated for gross thrombi. Organs were fixed in formalin, sagittally sectioned, and evaluated by a pulmonary pathologist blinded to treatment.Results Antegrade and retrograde flushes demonstrated no significant thrombi. Gross pathologic evaluation revealed no occlusive central thrombi. Scant peripheral thrombi were detected in both treatment groups. No microscopic thrombi were noted in either treatment group.Conclusions Delayed heparin administration after cardiac death does not affect thrombus formation in an animal model of lung procurement after cardiac death. Concern about clinically significant thrombosis occurring when heparin is not given before cardiac arrest appears unfounded. These findings suggest that DCD lungs can be used regardless of antemortem heparin administration.
Keywords: transplantation; lung; pulmonary arteries/veins; organ preservation